Synthesis of -TCP by Wet Precipitation Method from Natural Lime - Ayu Ratnasari; Naili Sofiyaningsih; Muhammad Syaifun Nizar; Hernawan Hernawan (Jurnal Keramik dan Gelas Indonesia, 2020)
Beta-tricalcium phosphate (β-TCP) is a biomaterial that is widely used as bone scaffold and calcium phosphate cement. β-TCP has excellent characteristic such as biocompatible, highly solubility, and faster degradation rate than other types of calcium phosphate. In this research, β-TCP was synthesized from natural limestone and phosphoric acid. The synthesis method used is wet precipitation method. Phosporic acid solution was added by titration at rate of 0,5 mL per second. Temperature reaction controlled at 60⁰C meanwhile calcination process at 800⁰C and 1000⁰C. The mineralogy characteristic by  X-Ray Diffractometer (XRD) showed that β-tricalcium phosphate main phase was formed at 800⁰C and while characterization of chemical content with X-Ray Flourescence (XRF) β-TCP has a Ca/P molar ratio of 1,35-1,37.